2022
DOI: 10.1152/ajpendo.00326.2021
|View full text |Cite
|
Sign up to set email alerts
|

Long-term light and moderate exercise intervention similarly prevent both hippocampal and glycemic dysfunction in presymptomatic type 2 diabetic rats

Abstract: A pre-diabetic population has an increased risk of cognitive decline as well as type 2 diabetes mellitus (T2DM). The present study investigated whether the progression of memory dysfunction and dysregulated brain glycogen metabolism is prevented with four months of exercise intervention from the pre-symptomatic stage in T2DM rat model. Memory function and biochemical and molecular profiles were assessed in the pre-symptomatic stage of OLETF rats, a T2DM model, with LETO rats as genetic control. These rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…Moreover, miR-382 paired with miR-370 has been confirmed as a sensitive biomarker for the detection of mild cognitive impairment (Salama et al 2020 ). Furthermore, our findings are consistent with previous research that found AE improved cognitive function in diabetic rats and increased expression of BDNF (Jesmin et al 2022 ). In line with our findings, a previous study also unveiled that decreased MALAT1 expression caused by exercise could suppress insulin resistance in T2DM via increasing miR-382-3p expression through synchronous inhibition of resistin (Liu et al 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, miR-382 paired with miR-370 has been confirmed as a sensitive biomarker for the detection of mild cognitive impairment (Salama et al 2020 ). Furthermore, our findings are consistent with previous research that found AE improved cognitive function in diabetic rats and increased expression of BDNF (Jesmin et al 2022 ). In line with our findings, a previous study also unveiled that decreased MALAT1 expression caused by exercise could suppress insulin resistance in T2DM via increasing miR-382-3p expression through synchronous inhibition of resistin (Liu et al 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moderate-intensity treadmill running for four weeks resulted in increased glycogen level and MCT2 protein expression in hippocampal tissue as well as an improvement in spatial memory in diabetic rats [ 72 ]. Light and moderate intensity treadmill running for 4 months from the presymptomatic stage in Otsuka-Long-Evans-Tokushima fatty (OLETF) rats (a T2DM model) normalized MCT2, glycogen, and BDNF levels, accompanied by the improvement of hippocampal-dependent memory dysfunction, suggest that exercise can prevent the progression of T2DM-relative cognitive decline by targeting hippocampal lactate-transport [ 73 ]. 8-week swimming exercise significantly increased MCT1, MCT2, and MCT4 protein expression in brain tissue of wild mice and AD mice, accompanied by improvement in learning and memory abilities in the water maze test [ 74 ].…”
Section: The Potential Mechanisms Of Lactate-mediated Exercise-induce...mentioning
confidence: 99%
“…There is a possibility that ANLS-related glycometabolism is variable against metabolic conditions. It has been reported that type 2 diabetes induces downregulated MCT2 levels in the rodent hippocampus (24)(25)(26). It is also known that the Western diet, which causes obesity, diminishes central MCT1 and MCT2 levels (27,28); diet-induced metabolic changes could modulate ANLS in the hippocampus.…”
mentioning
confidence: 99%